Fast Course for Authors: how to write a paper - Cruz, Isabel CF da (Online Brazilian Journal of Nursing, 2009)
HTML clipboard PROBLEM: the authors fail to write a manuscript in a way that is accessible to readers of a general journal. OBJECTIVE: Point out that scientific manuscripts published by OBJN must follow the IMRaD style (introduction, methods, results and discussion) or DMPAEP and should have a structured abstract and a structured discussion. METHOD: Fast class about writing a manuscript. CONCLUSION: The OBJN argues for including "writing for publication" as subject of the research methodology nursing discipline.